THE ESTIMATION OF CATARACT PATIENTS AWARENESS - Ковтун М. І. (World of Medicine and Biology, 2015)
The aim of research was the estimation of cataract patients’ awareness about the disease particularities and the influence of surgical treatment seeking terms and cataract stage on treatment outcome. The 791 patients who were hospitalized for cataract surgical treatment took part in questionnaire survey. The most part of patients was in age group from 61 to 80 y.o. (87%). 632 (80%) patients were retirement pensioners. 52% of respondents were aware about the cataract before, 32 % of respondents were not aware about this disease and 15,3% of respondents found it hard to answer. 50,5% of respondents were aware about the main symptoms of cataract, 28,5% were not aware about the symptoms and 21% of respondents found it hard to answer.The results of survey had shown, that the main part of patients (75,7%) received the information about cataract only during the visit to ophthalmologist with complaints on visual impairment or for new lens fitting. The 6% of respondents had noted, that the state hospital was selected because of difficult financial position.
Keywords: awareness; cataract; surgical treatment